USSR oil and gas industry training Systems in higher education - Vinogradov, V.N.; Porshakov, B.P. (Energy policy, 1990)
The importance of the oil and gas industries to the USSR both in terms of economic potential and social and political development is examined. The training of personnel in these key industries is therefore of great interest and importance. The authors outline a fundamentally new approach to training specialists. There is a need to equip specialists not only with the skills necessary for their particular discipline but also the broader management skills and the creativity to develop dynamic and flexible industries. An outline of the new structure in higher education is given.